Fundamentals of crystallography (International Union of Crystallography texts on crystallography, 2009)
Crystallography and structure theory have recently received increasing interest due to their role in understanding biological structures, high-temperature superconductors, and effects on mineral properties related to changes in temperature and pressure. This text offers an account of the wide range of crystallography in various branches of science.The fundamentals, the most frequently used procedures, and experimental techniques are all described, and a number of appendices are devoted to more specialist aspects. The book is an updated edition with emphasis on the range of topical applications. Illustrations should help to clarify the subject matter. To provide a better understanding of the basics of crystallography, a compact disk has been added to this edition, offering the facilities of modern graphics to simulate experiments, show complex images, and provide a number of exercises.